Pengaruh Aplikasi Pengelolaan Keuangan pada Pengembangan Kompetensi Mahasiswa dalam Meminimalisir Pengeluaran Pribadi - Najwa Widya Choirina; Sagita Shafa Prasetia (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to measure the extent to which financial management applications influence students' financial competence in making monthly budgets, recording expenses, and monitoring personal financial use. In addition, this study aims to analyze whether financial management applications can provide effectiveness in minimizing personal expenses by making students more disciplined in managing their finances. This study uses a quantitative research method with a descriptive approach. Information was obtained through a questionnaire distributed to students who use and do not use financial management applications throughout the University in Surabaya. The research sample was taken using a simple linear regression analysis technique with a total of 100-110 students as respondents. The information analysis techniques used include descriptive statistical tests to describe application usage patterns and simple linear regression tests to measure the effect of financial management applications on the development of student competence in managing expenses. The results of the research show that financial management applications are quite good in having an influence on student competency development.